Effects of low-level Er on the microstructure, mechanical and anti-corrosion properties of Mg-1Zn-0.3Zr alloy - Junguang He; Xuyang Li; Qinglei Gao; Wuyun Feng; Huan Li; Jiuba Wen (Journal of Materials Research and Technology)
To enhance the mechanical properties and corrosion resistance of biodegradable Mg alloys, varying amounts of Er (0, 0.5, 1, 1.5, 2, and 3 wt%) are added to the Mg-1Zn-0.3Zr alloy in this study. The phases of Mg3Er2Zn3 and MgEr are observed after Er doping. As the Er content increases, there is a progressive reduction in grain size, accompanied by a gradual increase in the volume fraction of second phases. The mechanical properties and corrosion resistance initially improve, followed by a gradual decline as the Er content continues to rise. The alloy with 1.5 wt% Er exhibits superior overall performance. Compared with the Mg-1Zn-0.3Zr alloy, the yield strength, ultimate tensile strength, and elongation increase by 18.3%, 34.3%, and 42%, respectively, while the corrosion rate decreases by 36.4%. The enhancement in mechanical properties is attributed to grain refinement and the strengthening of second phases. The improvement in corrosion resistance is linked to the formation of Er2O3, an elevated potential, and a lower potential difference between the second phases and Mg matrix. Furthermore, it is confirmed that Ca and P ions are enriched in the outer layer of corrosion products.